PillHarmonics: An Orchestrated Pharmacogenetics Medication Clinical Decision Support Service - Dolin, Robert H.; Shenvi, Edna; Alvarez, Carla; Barrows, Randolph C., Jr.; Boxwala, Aziz; Lee, Benson; Nathanson, Brian H.; Kleyner, Yelena; Hagemann, Rachel; Hongsermeier, Tonya; Kapusnik-Uner, Joan; Lakdawala, Adnan; Shalaby, James (Applied Clinical Informatics, 2024)
Objectives Pharmacogenetics (PGx) is increasingly important in individualizing therapeutic management plans, but is often implemented apart from other types of medication clinical decision support (CDS). The lack of integration of PGx into existing CDS may result in incomplete interaction information, which may pose patient safety concerns. We sought to develop a cloud-based orchestrated medication CDS service that integrates PGx with a broad set of drug screening alerts and evaluate it through a clinician utility study.Methods We developed the PillHarmonics service for implementation per the CDS Hooks protocol, algorithmically integrating a wide range of drug interaction knowledge using cloud-based screening services from First Databank (drug–drug/allergy/condition), PharmGKB (drug–gene), and locally curated content (drug–renal/hepatic/race). We performed a user study, presenting 13 clinicians and pharmacists with a prototype of the system's usage in synthetic patient scenarios. We collected feedback via a standard questionnaire and structured interview.Results Clinician assessment of PillHarmonics via the Technology Acceptance Model questionnaire shows significant evidence of perceived utility. Thematic analysis of structured interviews revealed that aggregated knowledge, concise actionable summaries, and information accessibility were highly valued, and that clinicians would use the service in their practice.Conclusion Medication safety and optimizing efficacy of therapy regimens remain significant issues. A comprehensive medication CDS system that leverages patient clinical and genomic data to perform a wide range of interaction checking and presents a concise and holistic view of medication knowledge back to the clinician is feasible and perceived as highly valuable for more informed decision-making. Such a system can potentially address many of the challenges identified with current medication-related CDS.
Keywords: pharmacogenetics; decision support system; electronic health records; FHIR